Demonstration of an As2S3-on-LiNbO3 Grating Coupler and its Application of Measuring a Grating-based Filter - Chen Zhang; C. K. Madsen (IEEE Photonics Journal)
We demonstrate the design, fabrication, and measurement results for an As2S3 grating coupler on a LiNbO3 substrate. The proposed coupler was fabricated by a single lithography step followed by a single reactive ion etching step, which substantially reduces the processing steps compared to previously reported coupling between vertically integrated As2S3 and LiNbO3 waveguides. The measured grating coupling loss is 3.75 dB at 1563 nm for TE polarization. In addition, a sidewall Bragg grating cavity was fabricated using the grating input and output couplers. The Bragg grating response had a full width at half maximum (FWHM) of 0.0375 nm around the resonance wavelength and a cavity free spectral range (FSR) of 0.36 nm. Applications of these vertically integrated As2S3 grating couplers include 2-D beam steering using the electro-optic tuning afforded by the LiNbO3 substrate and electro-optic sensing.